Reference to characters in narratives of Russian-Hebrew bilingual and Russian and Hebrew monolingual children with Developmental Language Disorder and typical language development. Issue 2 (April 2022) - Fichman, Sveta; Walters, Joel; Melamed, Ravit; Altman, Carmit
This research analyzed adequacy of referential expressions in the narratives of bilingual and monolingual children with Developmental Language Disorder (DLD) and typical language development (TLD), aiming to shed light on the relative contribution of morpho-syntactic, discourse-pragmatic, and semantic constraints. Narratives were collected from 51 children using a storytelling procedure ( MAIN – Multilingual Assessment Instrument for Narratives ). Participants were 18 bilingual Russian-Hebrew preschool children (8 with DLD), 17 monolingual Russian speakers (9 with DLD), and 16 monolingual Hebrew speakers (5 with DLD) aged 5;6–6;7. Referential expressions were coded for form (noun phrase [NP] or pronoun) and character function (Introduction or Maintenance). Analyses addressed the effects of proficiency group (TLD/DLD), language group (bilingual/monolingual), and language (Russian/Hebrew) on inadequate pronoun use and definiteness. Results demonstrated that children in all groups introduced characters using NPs. Children with DLD used more morpho-syntactically inadequate pronouns, such as incorrect gender, while both children with DLD and those with TLD used similar numbers of discourse-pragmatically inadequate pronouns. Bilinguals used more morpho-syntactically inadequate pronouns than monolinguals. In Hebrew, bilingual children with DLD omitted definite articles for character Maintenance more frequently than bilingual children with TLD and monolingual Hebrew-speaking children with DLD. Wrong gender assignment indicates that children with DLD have difficulties with morpho-syntactic constraints. Omission of definite articles for character Maintenance indicates a possibility of both morpho-syntactic and semantic difficulties that bilingual children with DLD acquiring Hebrew face. The results offer insight into the nature of the difficulty observed in bilingual children with DLD in using referential expressions.